Assessment Practices and Trends in Undergraduate Economics Courses - Schaur, Georg; Watts, Michael; Becker, William E (American Economic Review, 2008)
Assessment Practices and Trends in Undergraduate Economics Courses by Georg Schaur, Michael Watts and William E. Becker. Published in volume 98, issue 2, pages 552-56 of American Economic Review, May 2008